Cybister (s. str.) poblanus sp. n. from Mexico and notes on other species of Cybistrinae (Coleoptera: Dytiscidae) - Arce-Pérez, Roberto; Novelo-Gutiérrez, Rodolfo; Fery, Hans (Zootaxa, 2021)
Cybister (s. str.) poblanus sp. n. is described from the Puebla state in Mexico. The species belongs to a group of members of the genus Cybister Curtis, 1827, which occur only in North America (including the Caribbean Islands) and are characterised by having several distinct ridges on the metacoxae (stridulatory organ) in males. The new species is the third of the genus reported for Mexico and the fourth for North America. It can easily be separated from its congeners by its great size and the shape of the male aedeagus. The habitus, the male genitalia and other details of C. poblanus sp. n. are illustrated and photographs of the male genitalia of the other three Cybister are given for comparison. Megadytes (Bifurcitus) lherminieri (Guérin-Méneville, 1829) and M. (B.) magnus Trémouilles & Bachmann, 1980 are the only other big species of subfamily Cybistrinae which occur in North America. They are externally similar to the new species and can easily be confused with it, hence the illustrations of their aedeagi to facilitate identification. A key to species is given for all species of Cybistrinae occurring in America north of Belize and Guatemala, including Cuba and the Bahamas. Lectotypes are designated for Cybister flavocinctus Aubé, 1838, Cybister explanatus var. fusculus Zimmermann, 1919, and Cybister (Megadytes) aubei Wilke, 1920. Notes are given on material of some Neotropical and Nearctic species of Cybister and Megadytes stored in different museums.